Anti diabetic Activity Of Green Tea And Black Tea (In Vivo) - Oktaviani, Sulha Rahmi; Nabilah, Uray Ulfah (FoodTech: Jurnal Teknologi Pangan, 2024)
Diabetes is a chronic medical condition that affects the way the body processes glucose. In recent years, there have been various advances in the diagnosis, management and treatment of diabetes, especially type 1 and type 2 diabetes. Green tea and black tea have long been known to have various health benefits, including potential anti diabetic effects. This article presents a review of the anti diabetic activity of green tea and black tea based on in vivo studies. Green tea, which is rich in polyphenols such as epigallocatechin-3-gallate (EGCG), is known to improve glucose tolerance and reduce insulin resistance. These effects are mediated by an increase in GLUT4 expression, as well as a reduction in insulin resistance index. Black tea with distinctive ingredients such as theaflavin and thearubigin, shows potential in inhibiting carbohydrate hydrolysis enzymes, increasing insulin secretion, and improving pancreatic function. Studies using animal models of diabetes have shown that tea consumption can lower blood glucose levels, improve glucose tolerance, and prevent damage to pancreatic beta cells. Although various studies have supported these benefits, there are inconsistencies in the results of epidemiological studies in humans. This could be due to variations in tea processing methods, tea chemical composition, as well as differences in research conditions. Therefore, further research is needed to understand the mechanisms underlying the anti diabetic effects of green tea and black tea and develop more controlled clinical applications.